Development of hyperpolarised xenon 129 production and MRI for a clinical setting - Irwin, Robert (2021)
When the spin polarisation of a nuclear species' is increased far above levels observed at thermal equilibrium, it is said to be hyperpolarised (HP). These HP species can be created using many different methods for the purposes of nuclear magnetic resonance (NMR) and magnetic resonance imaging (MRI). HP Xenon 129 (129Xe) can be created using spin-exchange optical-pumping (SEOP), which uses circularly polarised light to polarise the electronic spins of alkali metal vapour. The polarised alkali metal electrons then transfer their polarisation to noble gas nuclei via Fermi contact two and three-body interactions. Other methods of HP are available such as dynamic nuclear polarization (DNP) and brute force (BF) polarisation.